Endocrine and metabolic effects of growth hormone treatment - Ismail, I.S.; Scanlon, M.F. (1993)
Short stature secondary to pituitary growth hormone (GH) deficency or Turner's syndrome remains the main indication for treatment with GH. However, recombinant human GH is finding other uses in both children and adults, so it is important to understand the effects of GH on metabolic and endocrine function